2021
DOI: 10.18174/546572
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of enteric methane emissions of Dutch dairy cows : Climate Envelop project 2019

Abstract: De Nederlandse landbouw staat voor de uitdaging om methaanuitstoot in 2030 met 2,1 Mton te verminderen en nog verder in 2050. Omdat methaanuitstoot van melkkoeien het belangrijkste onderdeel is van deze voetafdruk, hebben boeren dringend behoefte aan efficiënte en kosteneffectieve opties om de methaanuitstoot verminderen. Fokkerij, waarbij gebruik wordt gemaakt van de natuurlijke variatie van dieren in methaanemissies, is een strategie die kosteneffectief, permanent en cumulatief is. Het doel van deze studie w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
0
0
1
Order By: Relevance
“…Daarnaast kan de Sniffer op een bedrijf blijven, waardoor er gedurende langere tijd een continue datastroom is van alle productieve melkkoeien die aanwezig zijn op een bedrijf. De nauwkeurigheid van Sniffer-metingen kan wat laag zijn, doordat de positie van de kop van de koe en de achtergrondconcentratie bepalend zijn voor de meting (de Haas et al, 2021).…”
Section: Snifferunclassified
“…Daarnaast kan de Sniffer op een bedrijf blijven, waardoor er gedurende langere tijd een continue datastroom is van alle productieve melkkoeien die aanwezig zijn op een bedrijf. De nauwkeurigheid van Sniffer-metingen kan wat laag zijn, doordat de positie van de kop van de koe en de achtergrondconcentratie bepalend zijn voor de meting (de Haas et al, 2021).…”
Section: Snifferunclassified
“…With development of economical, low CH 4 concentration enrichment technologies still in their infancy (NORCE Norwegian Research Centre 2020, Wang et al, 2020, Yang et al, 2022, developing local ventilation techniques at the animal level capable of extracting breath CH 4 from cows before air mixing could be an option. In fact, a large body of literature already confirm that measured CH 4 concentrations close to cattle nostrils, as well as in enclosers such as feed bins and respiratory chambers ranged from 300 to 1500 ppm, compared to indoor CH 4 values of 15 to 201 ppm in naturally ventilated cattle barns (López-Paredes et al, 2020, van Breukelen et al, 2023, Teye et al, 2008, Blaise et al, 2018, Sorg et al, 2017, De Haas et al, 2019.…”
Section: Introductionmentioning
confidence: 95%
“…Apart from Wu et al (2016) who reported CH 4 concentrations around the lying cubicle, previous measurements of CH 4 concentrations in cattle buildings have been primarily concerned with calculating emissions. Therefore, gas sampling points are often positioned either beyond the AOZ at ventilation openings or in feed bins (López-Paredes et al, 2020, van Breukelen et al, 2023, Sorg et al, 2017, De Haas et al, 2019, Huang and Guo, 2018, Ngwabie et al, 2009. As a result, detailed information on CH 4 concentration levels and other gas compositions near animals are scarce for emerging technologies aimed at CH 4 capture and utilisation in commercial cattle barns (Nisbet et al, 2020, Pratt and Tate, 2018, NORCE Norwegian Research Centre 2020, Galama et al, 2020.…”
Section: Introductionmentioning
confidence: 99%